THU0681 Baseline ESSDAI/DAS scores in 8061 patients with primary sjÖgren syndrome: characterization of systemic disease. (15th June 2017) - Brito-Zerόn, P; Acar-Denizli, N; Zeher, M; Rasmussen, A; Li, X; Baldini, C; Gottenberg, J-E; Danda, D; Quartuccio, L; Hernandez-Molina, G; Kruize, AA; Park, S-H; et al.
Abstract : Objectives: To characterize and quantify systemic involvement at diagnosis in a large international cohort of patients with primary Sjögren's syndrome (SS). Methods: The Big Data Sjögren Project was formed in 2014 to take a "high-definition" picture of primary SS at diagnosis by merging international databases (9302 consecutive patients from 21 countries of the 5 continents). The main features (including ESSDAI/DAS) at diagnosis were analysed. Results: Baseline ESSDAI was available in 8061 patients (93% female, mean age 53yrs). The mean ESSDAI score at diagnosis of the entire cohort was 6.4±7.9. In 1498 patients (19%), score at diagnosis was 0, while 681 (8%) presented with high activity in at least one domain. The main systemic features at diagnosis were biological (51%), articular (38%), haematological (24%) and glandular (22%). Low DAS was reported in 4480 (56%) patients, moderate DAS in 2483 (31%) and high DAS in 1098 (14%) patients. The mean baseline ESSDAI was higher the younger the patient was (p<0.001), higher in White patients (6.9 vs 5.1, p<0.001), males (8.4 vs 6.2, p<0.001), those with positive ocular (6.7 vs 4.9, p<0.001) or oral (6.8 vs 6.2, p=0.016) tests, and those with ANA (6.9 vs 4.5, p<0.001), RF (7.5 vs 5.8, p<0.001) and anti-Ro/La antibodies (7.2 vs 4.4, p<0.001). Logistic regression identified as independent variables White ethnicity (OR 3.07), abnormal ocular tests (OR 2.14), ANA (OR 1.67) and Ro/La autoantibodies (OR 2.78). Conclusions: This is the largest series of patients with primary SS in whom the ESSDAI score has been evaluated. Primary SS is undeniably a systemic disease even at the time of diagnosis, with nearly 80% of patients showing an ESSDAI score >0. Disclosure of Interest: None declared